2022
DOI: 10.1007/s11356-022-24602-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of landscape pattern changes and environmental indices on land surface temperature in a fragile ecosystem in southeastern Iran

Abstract: Environmental indices and landscape pattern changes alter Land Surface Temperature (LST). Thus, the accurate evaluation of the relationship between these factors and LST is considered as important for managing ecosystems, especially the fragile ones under high stress. In the present study, Landsat TM5 satellite images (1989), Landsat 8 OLI/TIRS ones (2019), and Google Earth Engine (GEE) system were used to prepare the maps of temporal-spatial LST changes, Land Use/Land Cover (LULC), and selected environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Several studies wer e reported on the environmental sustainability aspects such as Eco-Hydrological sustainability (Khatun et al, 2021;Shiran et al, 2021), eco-environmental vulnerability (Nguyen et al, 2016;Liou et al, 2017;Venkatesh et al, 2020;and Kurn iawan et al, 2022), vegetation dynamics (Qureshi et al, 2020), Soil moisture-LST based drought characterization (Saha et al, 2018). Several hydrological, ecological, environmental, and socio-economic problems and their solutions have been addressed by analyzing the Remote Sensing based land cover changes for environmental sustainability (Liou et al, 2017;Venkatesh et al, 2020;Kurniawan et al, 2022;Saleh et al, 2022). It includes changes in the built-up area, wetlands, f o r es t cover, agricultural cropping patterns, and hydrological responses.…”
Section: Introduction 11 Environmental Sustainability Assessmentmentioning
confidence: 99%
“…Several studies wer e reported on the environmental sustainability aspects such as Eco-Hydrological sustainability (Khatun et al, 2021;Shiran et al, 2021), eco-environmental vulnerability (Nguyen et al, 2016;Liou et al, 2017;Venkatesh et al, 2020;and Kurn iawan et al, 2022), vegetation dynamics (Qureshi et al, 2020), Soil moisture-LST based drought characterization (Saha et al, 2018). Several hydrological, ecological, environmental, and socio-economic problems and their solutions have been addressed by analyzing the Remote Sensing based land cover changes for environmental sustainability (Liou et al, 2017;Venkatesh et al, 2020;Kurniawan et al, 2022;Saleh et al, 2022). It includes changes in the built-up area, wetlands, f o r es t cover, agricultural cropping patterns, and hydrological responses.…”
Section: Introduction 11 Environmental Sustainability Assessmentmentioning
confidence: 99%